PRACTICAL SAMPLING FOR AUDITORS. - Herbert, Leo (The Accounting Review, 1946)
Abstract In the course of an audit, an auditor may analyze in detail each item in the books. However, in most instances, to arrive at a conclusive opinion in regard to the records, it is unnecessary to collect complete information on each item with which the auditor deals. To overcome the necessity of checking each item in every investigation, accountants and auditors have employed the method of test checking or sampling. From the test check or sample, a relatively small part of the records, the auditor draws a conclusion as to the general accuracy of the accounting details. To appreciate the auditor's problems of sampling, one must know about sampling theory as applied to data which an accountant will probably encounter. Sampling theory is basically related both to the theory of probability and to the likelihood of errors. Whenever each item chosen has the same probability of being chosen as any other item in the group, the relationship between the items may be worked out to a precise mathematical point.